New constraints on the basal sole thrust at the eastern Caledonian margin in northern Sweden - Bierlein, Frank; Greiling, Reinhard O. (Geologiska Föreningens i Stockholm förhandlingar, 1993)
Detailed structural mapping aided by electromagnetic anomaly maps revealed the structure of the Lower Allochthon at the eastern, external Caledonian margin in N Sweden (64°45′-65°N) to be a hinterland-dipping duplex with minor subduplexes and ‘slices’ of tectonically thickened alum shales. These latter complexities are apparently related to the soft, ductile nature of the alum shale of the mid to upper Cambrian Fjällbränna Formation through which the sole thrust propagated in the present area. The topography of the regional sole thrust is characterized by extremely low dips (0.5°-1.5°), consistently towards the WNW. In places where, apparently, the bedding dip is steeper than that of the sole thrust, the sole thrust cut stratigraphically downsection (but topographically upwards).
Elektronische Reproduktion der Druck-Ausgabe 4. Januar 2010
Gesehen am 22.02.2023